Biomaterial Real Cracks Evaluation by Eddy Current Testing Method - Milan Smetana; Klara Capova (Communications - Scientific letters of the University of Zilina, 2015)
The paper deals with identification of real biomaterial`s cracks using electromagnetic non-destructive sensing. Advanced types of the magnetic field sensors are used for this purpose. New modular eddy current probe is used for the evaluation. Harmonic excitation is used for the excitation of the eddy currents. The real biomaterial stress corrosion cracks (SCC) and fatigue cracks (FC) are inspected. Gained results are discussed and presented in the paper. The main aim of the paper is to compare the sensitivity of the various magnetic field sensors under the same conditions.